2007
DOI: 10.1016/s0377-1237(07)80143-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Four Elastomeric Interocclusal Recording Materials

Abstract: Background: The fabrication of dental prosthesis requires the transfer of interocclusal records from patient's mouth to semiadjustable articulators using different kinds of recording media. Any inaccuracy in these interocclusal records leads to occlusal errors in the final prosthesis. This study was conducted to evaluate the dimensional changes occurring in the interocclusal recording material over a given period of time and the material's resistance to compression during the cast mounting on the articulator. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…The deformation may vary with the thickness and the properties of the recording materials used. 4 The testing of the resistance to compression after setting was performed following a modification of the method described in A.D.A specification no 19 for the elastomeric impression materials. 1,15 For standardization, the specimens were stored at room temperature for 24hrs to simulate the time between clinical and laboratory phases.…”
Section: Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation
“…The deformation may vary with the thickness and the properties of the recording materials used. 4 The testing of the resistance to compression after setting was performed following a modification of the method described in A.D.A specification no 19 for the elastomeric impression materials. 1,15 For standardization, the specimens were stored at room temperature for 24hrs to simulate the time between clinical and laboratory phases.…”
Section: Discussion:-mentioning
confidence: 99%
“…2 It has been shown that the compression resistance decreases as the thickness increases. 4 Interocclusal registration materials act as a significant source of cross contamination, so these must be disinfected immediately after their removal from mouth. Occupational safety and health association (OSHA) guidelines in 1996 required dentist, dental laboratory employers and other employers in health care fields to provide protection for their employees against the possibility of infection transmission by implementation of conscientious and consistent barrier controls.…”
mentioning
confidence: 99%
“…Materials that have been intended for intermaxillary recording procedures include plaster, modeling compound, waxes, acrylic resin, zinc oxide-eugenol pastes, [2] rubber base, and silicone materials. [3] Newer ones include polyether and polyvinyl siloxane for ideal maxillomandibular registration.…”
Section: Introductionmentioning
confidence: 99%
“…Maxillomandibular records are necessary to study the status of the dentition and to construct dental restoration. One type of record is used for mounting casts of the teeth or setting the articulator adjustments and another for appraising the degree of occlusal or incisal tooth contacts 2 . Adequate laboratory facilities are commonly not available locally and casts have to be sent to others laboratories for articulation.…”
Section: Introductionmentioning
confidence: 99%
“…In these situations, the patients' interocclusal records are made and sent along with the cast to the laboratory. This requires that the records must be dimensionally stable for the given period of time before they are used to articulate the casts 2 . Recording maxillomandibular relationship is an important step in oral rehabilitation.…”
Section: Introductionmentioning
confidence: 99%